Upregulation of P53 Gene Expression on Breast Cancer Stem Cells Treated with Trisindoline 5 Compound - Salsabila, Yofinta I; Azhaar, Nadia; Fatoni, Muhammad; Nurhayati, Awik P.D.; Ghaissani, Shabrina Syifa; Andifa, Vinda Aprilia Nurul; Santoso, Mardi; Martak, Fahimah (Stem Cell and Cancer Research (SCCR), 2022)
Background: Cancer stem cells (CSCs) are the subpopulation of cancer cells that have been demonstrated as the cause of tumor formation. The most common cancer for women and the second leading cause of death in breast cancer. Numerous genes have been involved in breast cancers, including p53. In cancer cells, p53 as well-known as the tumor suppressor gene plays an important role in directing cells with DNA damage into apoptosis. Trisindolines are heterocyclic nitrogen compounds consisting of an isatin core bearing two indole moieties that provide cytotoxic effects on cancer cells. Recently research had led to the development of the new modification of trisindoline compound into trisindoline 5. Objective: This study aims to investigate the effect of trisindoline 5 compounds against p53 gene expression in CSCs MDA-MB-231 in vitro. Methods: CSCs MDA-MB-231 were divided into control and treatment groups which were further analyzed in gene expression using the qPCR Livak method. Results: Based on gene expression analysis, trisindoline 5 increases the expression of p53 in CSCs MDA-MB-231. Conclusion: This study informed that trisindoline 5 could upregulate the expression of tumor suppressor gene p53 in CSCs MDA-MB-231 in vitro.